Micellar-polymer for enhanced oil recovery for Upper Assam Basin; Resource-Efficient Technologies; Vol. 3, iss. 1 : TECHNOSCAPE 2016: International Conference on Separation Technologies in Chemical, Biochemical, Petroleum and Environmental Engineering - Das B. M. (2017, 2017)
Title screen